INDUCTION OF FISH PELLET MAKING MACHINE TO IMPROVE FEED COMMUNITY PROGRAM IN CATFISH FARMERS IN MOJOKERTO REGENCY - Andi Kurniawan; Riski Agung Lestariadi (Journal of Innovation and Applied Technology, 2017)
This article is related to the IbM program entitled Community Feed of Mina Mahardika Catfish Aquaculture Group in Seduri village, Mojosari district, Mojokerto Regency. Based on the identification of partner problems, the main problem facing by Mina Mahardika Group was the characteristics of fish feed produced by the group. The fish feed was very easy to be broken, suspended in the water and does not have enough buoyancy. The problems mainly because the production of the fish feed was still used a conventional technique. The IbM program reported in this article was intended to solve the problems by inducing the pellet making machine that can produce the fish feed having good texture and enough buoyancy for catfish aquaculture activity. The result of the IbM program indicated that the program can help the Mina Mahardika Group to solve their main problems and improve the aquaculture activity through community feed program.